Ecological assessment of pit lakes in Raniganj, India: Application of different indices and multivariate statistics - Saikat Mondal; Debnath Palit (Water Science, 2023)
ABSTRACTCoal mine generated open pit lakes are well distributed in Raniganj coal field area, West Bengal, India. This paper screened out ecological state macrophyte index (ESMI), water quality index (WQI) and multivariate statistical methods to assess the ecological status of four pit lakes, Nagrakonda, Joyalbhanga, Dalurbandh, and Kumardihi. Seven water quality parameters (pH, total dissolved solids, dissolved oxygen, Secchi depth nitrate, chloride, and phosphate) and six sediment quality parameters (pH, organic carbon, bulk density, particle density, available nitrogen and phosphorus) were analyzed for one year on a monthly basis from four pit lakes. The abundance and diversity of aquatic macrophytes were also analyzed. In the studied pit lakes, water and sediment quality variables showed significant spatial variation. WQI showed that the water quality in all pit lakes was good and according to ESMI these lakes were categorized into good ecological status. The results of this study indicated the values of water quality and macrophyte based indices highlighted the ecological condition of the pit lakes of the study sites thus should be considered it as reliable tool for assessing of the ecological status of any wetlands.